THE USE OF LISTEN READ DISCUSS STRATEGY AND READING MOTIVATION TOWARD THE STUDENTS' READING COMPREHENSION - Robby Ibrahim (Universitas Lancang Kuning, 2017)
In teaching reading, teaching strategy and reading motivation influences students’ reading comprehension. Strategy which was used in this quasi experimental research is Listen Read Discuss. It can be used as a variation of teaching strategy in teaching reading comprehension of descriptive text. The purpose of this research was to find out the effect of using Listen Read Discuss and students’ reading motivation on students’ reading comprehension of descriptive text. This research was an experimental research with factorial design two by two. It was conducted at SMK Muhammadiyah 2 Pekanbaru. Population of this research was second grade students with the total population was 137. The sample was taken by cluster random sampling; the total number of sample was 52 (26 students in II.1 class and 26 students in II.2 class). The results of this research are, first, the students who were taught by using Listen Read Discuss had better result on reading comprehension of descriptive text than the students who were taught by using small group discussion. Second, the students with higher reading motivation who were taught by Listen Read Discuss had better reading comprehension of descriptive text than those who are taught by using small group discussion. Third, students with lower reading motivation who are taught by Listen Read Discuss had better reading comprehension of descriptive text than those who are taught by using small group discussion. Fourth, there was no interaction between both techniques and students’ reading motivation on students’ reading comprehension of descriptive text. In conclusion, Listen Read Discuss can be used as a teaching strategy in teaching reading comprehension of descriptive text at SMK Muhammadiyah 2 Pekanbaru. For further researcher, they are suggested to do more research dealing with this strategy on other skills and others kinds of text.